Does the "Devil" originate from the fallopian tubes?. (December 2021) - El Bairi, Khalid; Al Jarroudi, Ouissam; Le Page, Cécile; Afqir, Said
Abstract: Epithelial ovarian cancer (OC) is a heterogeneous disease and continues to be mostly diagnosed in advanced stages. The high lethality, the high rate of platinum-resistance, and the poor survival outcomes are the principal factors for categorizing OC among the most aggressive gynecological cancers. Only recently, a substantial progress has been made in our latest understanding of the origins of OC, particularly of high-grade serous histology. For a long time, the accumulation of genetic alterations in epithelial single layer cells of ovarian cysts caused by cyclic ovulations was considered as the most important driver and the long-standing dogma of ovarian tumorigenesis. Besides, the unique biological features and high histological heterogeneity of OC did not support this hypothesis. Indeed, various extra-ovarian cells of origin and multiple sites to each histotype were proposed, supported by cogent evidence from clinical cohorts and animal studies. In light of this enigma, this review was conducted to discuss the recent evidence supporting the revised origins of ovarian carcinoma histotypes with a particular focus on high-grade serous OC which may impact diagnostic and preventive approaches.